2014
DOI: 10.1007/s00894-014-2452-9
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid coarse-grained/atomistic model of “chitosan + carbon nanostructures” composites

Abstract: We present a new hybrid molecular dynamics model of chitosan oligomers which is constructed specifically for studying chitosan + carbon nanostructures composites, their structure and mechanical properties. The model is derived for application within the modified molecular mechanics force field AMBER. Method of virtual sites mapping allowed to retain hexagonal rings of chitosan backbone. Mass and structural disposition of virtual atoms has been found as function of joined groups' atoms masses and coordinates. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Here, we use our coarse-grained model of chitosan to investigate how the sequence of GlcNAc monomers affects chitosan self-assembly in solution, the structure of the resulting hydrogel network, and the ability of molecules to diffuse within the network. To the best of our knowledge, the effect of monomer sequence on chitosan self-assembly has not been discussed previously in experimental ,,, or simulation , studies. Thus, we do not believe that there are any experimental methods of controlling the sequence of GlcNAc monomers.…”
Section: Introductionmentioning
confidence: 97%
“…Here, we use our coarse-grained model of chitosan to investigate how the sequence of GlcNAc monomers affects chitosan self-assembly in solution, the structure of the resulting hydrogel network, and the ability of molecules to diffuse within the network. To the best of our knowledge, the effect of monomer sequence on chitosan self-assembly has not been discussed previously in experimental ,,, or simulation , studies. Thus, we do not believe that there are any experimental methods of controlling the sequence of GlcNAc monomers.…”
Section: Introductionmentioning
confidence: 97%
“…26 This model uses a total of 7 spheres to represent each GlcN monomer, and is parameterized to accurately represent the interactions between chitosan and carbon nanostructures such as graphene nanoparticles and carbon nanotubes. 26 The atomistic simulations used to derive the hybrid model were performed in AMBER, but Coulomb interactions were neglected because the carbon nanostructures are not charged. 26 The authors found that the total molecular energies resulting from the atomistic and coarse-grained models differed by less than 1%, and the bulk densities of the chitosan molecules in the atomistic and coarse-grained models differed by less than 5%.…”
Section: Introductionmentioning
confidence: 99%
“…26 The atomistic simulations used to derive the hybrid model were performed in AMBER, but Coulomb interactions were neglected because the carbon nanostructures are not charged. 26 The authors found that the total molecular energies resulting from the atomistic and coarse-grained models differed by less than 1%, and the bulk densities of the chitosan molecules in the atomistic and coarse-grained models differed by less than 5%. 26 Marrink and coworkers have developed a more general way to coarse-grain carbohydrates by extending the MARTINI force field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petrov et al employed density functional theory (DFT) and DFT-based tight-binding to determine crystal structure configurations and hydrogen-bonding of chitin from a first-principles approach. On the other end of the multiscale methods, Yu and Lau have developed a coarse-grained model for chitin, allowing the simulation of 300 nm long chitin chains, while Kossovich et al , have developed a hybrid atomistic/coarse-grained model for chitosan, allowing simulations of 200 nm long chitosan chains. Recent studies have also performed conformational and interaction analysis of chitosan with carbon nanotubes in aqueous solution for applications in drug delivery and structural reinforcement.…”
Section: Introductionmentioning
confidence: 99%